The Effect Of Work Discipline And Work Motivation On Employee Performance At PT. Tri Adi Bersama Branch Office, Tangerang Regency - Shakti, Dikha Berwira; Hanis, Umar (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2025)
This study aims to analyze the effect of work discipline and work motivation on employee performance at the PT Tri Adi Bersama Branch Office, both individually and simultaneously. This study uses a quantitative approach with a data collection method through questionnaires distributed to 63 employees. Data analysis was carried out using multiple linear regression, including the coefficient of determination (R²) test, t-test, and F-test. The results of the regression analysis show the equation Y = 8.440 + 0.566 X₁ + 0.236 X₂ with an R² value of 0.762, which means that work discipline and work motivation together affect employee performance by 76.2%, while 23.8% is influenced by other factors. The t-test shows that work discipline (X₁) and work motivation (X₂) have a significant effect on employee performance, with each calculated t value of 12.817 and 10.153 which is greater than the t table of 2.000. The F test also shows a significant simultaneous effect with a calculated F value of 96.005 which is greater than the F table of 3.150. Thus, work discipline and work motivation are proven to have a significant effect on employee performance, both individually and together